2022
DOI: 10.1021/acs.est.1c08614
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Dietary Exposure and Health Risk of Polychlorinated Naphthalenes

Abstract: Intake from food is considered an important route of human exposure to polychlorinated naphthalenes. To our knowledge, several studies have quantified dietary exposure but only in European countries and measuring only a few of the 75 congeners. In addition, the influence of source diversity on human exposure has seldom been assessed. We analyzed 192 composite food samples composed of 17,280 subsamples from 24 provinces in China to measure the concentrations of polychlorinated naphthalenes and estimate their da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
(91 reference statements)
4
11
1
Order By: Relevance
“…The ∑UV filter concentrations in the 184 composite food samples from eight food categories were 1.5–68.3 ng/g ww, and the median was 7.9 ng/g ww. The concentrations of several emerging pollutants were determined in the same food samples in previous studies. The ∑UV filter concentrations were lower than the chlorinated paraffin concentrations but similar to the bisphenol diglycidyl ether and organophosphate ester concentrations and one-3 orders of magnitude higher than the bisphenol A, fipronil insecticide, polybrominated diphenyl ether, polychlorinated naphthalene, and perfluoroalkyl substance concentrations. This indicated that large amounts of UV filters are produced and used in China.…”
Section: Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The ∑UV filter concentrations in the 184 composite food samples from eight food categories were 1.5–68.3 ng/g ww, and the median was 7.9 ng/g ww. The concentrations of several emerging pollutants were determined in the same food samples in previous studies. The ∑UV filter concentrations were lower than the chlorinated paraffin concentrations but similar to the bisphenol diglycidyl ether and organophosphate ester concentrations and one-3 orders of magnitude higher than the bisphenol A, fipronil insecticide, polybrominated diphenyl ether, polychlorinated naphthalene, and perfluoroalkyl substance concentrations. This indicated that large amounts of UV filters are produced and used in China.…”
Section: Results and Discussionmentioning
confidence: 84%
“…44 The total UV filter concentrations were lower in our samples than in marine and freshwater biota from Norway 24 and fish from Spain. 20,45 The concentrations of polychlorinated naphthalenes 40 and organophosphate esters 36,46 were also lower in Chinese foods than previously found in samples from European countries. These results were consistent with previous findings 11,15 that UV filters can bioaccumulate and biomagnify through the food chain and indicate that UV filters are used extensively in Europe.…”
Section: ■ Introductionmentioning
confidence: 90%
“…, drinking water and showering). Meanwhile, dietary ingestion is the leading cause of population exposure to toxic chemicals sourced from food production, 72 especially people who have a specific dietary style, such as drinking water with teabags 73 and eating grilled food. 74…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 44 proposed a modeling method for quantifying the population exposure to trihalomethanes (THMs) when swimming in a pool, which would further differentiate their transfer and distribution in the body via diverse behaviors (e.g., drinking water and showering). Meanwhile, dietary ingestion is the leading cause of population exposure to toxic chemicals sourced from food production, 72 especially people who have a specic dietary style, such as drinking water with teabags 73 and eating grilled food. 74 In summary, quantitative in vitro to in vivo extrapolation (QIVIVE) may be fully implemented in risk assessment.…”
Section: Limitations and Additional Considerationsmentioning
confidence: 99%
“…Due to their environmental persistence, long-range transport, high toxicity, and bioaccumulation, PCNs were prohibited for industrial production and added to the regulated list of the Stockholm Convention on Persistent Organic Pollutants (POPs) in May 2015 . However, PCNs remain ubiquitous in current environments due to the legacy of historical production and unintentional thermal release processes. , To date, PCNs have been detected in various abiotic environmental matrices, including air, water, and soil, as well as in biological matrices, including plants, animals, and humans. , Furthermore, PCNs exhibit dioxin-like toxicities, such as dermal lesions, endocrine disruption, hepatotoxicity, immunotoxicity, embryotoxicity, teratogenicity, and carcinogenicity. Given the potential threats of PCNs to biological health, their bioaccumulation and biomagnification behaviors are of particular concern. Previous reports have explored the trophic transfer of PCNs in Chinese marine fish, Canadian lake biota, and benthic and pelagic food chains from the Baltic Sea. …”
Section: Introductionmentioning
confidence: 99%